(untitled) (Journal of Economic Research & Business Administration, 2015)
This paper reviews Kazakhstan’s tax system. Transition to market economy taxation is one of the most important and a complex problem as it is related to the formation of the financial resources of the country. The steady increase in the role of taxes in the socio-economic development of society leads to success of market reforms implemented in the country. In Kazakhstan, taxation is governed by the Tax Code, which came into force on the 1st of January 2009. Kazakhstan is also a party to more than 35 double tax treaties with various countries. The double tax treaties prevail over the Tax Code, but their application must comply with established procedures. The tax system in Kazakhstan can be broken down into company tax, income tax, payroll tax. Such taxes as corporate income tax, value added tax, personal income tax, and excise taxes account for the largest portion of budget revenues. After a general introduction which gives an overall view on the Kazakhstan economy, the second section describes the current tax policy and influence of tax system on economic growth of country. The final section concludes ideas